Outage analysis of multihop full duplex relaying - Baranwal, Tarun Kr.; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Communications Letters, 2013)
We consider a multihop full duplex relaying (FDR) system, where multiple full duplex decode-and-forward relays are connected in cascade so as to forward the information from a source terminal to a destination terminal. Since FDR causes additional quotedblleft echoquotedblright interference at the relay, we introduce a parameter that captures the ability of the relays to isolate transmission from reception. This parameter is defined as the ratio of the received desired signal power to the received interference power, when the transmit power is the same for the useful and the interfering signals, and dubbed as quotedblleft path-loss-to-interference ratioquotedblright (PLIR). For given values of the PLIR, we investigate the number of full duplex relays that lead to the minimum outage probability. The performance of multihop half duplex relaying (HDR) is also studied as a benchmark, showing that FDR outperforms HDR, in terms of the outage probability, for sufficiently large values of PLIR. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Full-duplex relaying; multihop communications